HUBUNGAN ANGKAT ANGKUT PASIEN DENGAN KELUHAN MUSCULOSKELETAL DISORDERS (MSD’S) PADA PERAWAT RUANG RAWAT INAP RSUD TELUK KUANTAN TAHUN 2018 - Sri Eka Putri; Tjipto - Suwandi; Makomulamin - - (LPPM Universitas Muhammadiyah Riau, 2018)
Musculosceletal complaints are a complaint on the skeletal muscle sections felt by a person starting from a very mild to very painful complaint. If the muscles receive static loads repeatedly and over a long period of time, they can cause complaints of joints, ligaments and tendons. The purpose of this study was to determine the correlation between job factors (work postur of patient lifting and load weight) and individual factors (age, body mass index (BMI), exercise habits and working period) with musculosceletal disorders (MSD’s) complaint on inpatient room nurses at Teluk Kuantan General Hospital. The type of research is a quantitative using method observasional analytic with cross sectional study design. Research was conducted on June-July 2018. In this study a sample of 56 nurses inpatient rooms at Teluk Kuantan General Hospital, all nurses were used as research samples. Data was analyzed by univariate, bivariate, and multivariate. The result of this research was 66,1% proportion of musculosceletal disorders complaining. Variables related to musculoskeletal complaints are work posture and working period. Confounding variables are weight and age. Unrelated variables are body mass index and exercise habits. The conclusion of this study is that the work period is the most dominant variable influencing musculoskeletal disorders with (p-value=0,007; OR: 17,949; 95% CI: 2,212-145,619). It is recommended for nurses to pay attention to the correct way of lifting patients so that they can adjust to body posture, and for K3RS should more active in providing training related to ergonomic patient handling.